Comparative analysis of multiphase machines - Saeed Khan, Kashif (My University, 2008)
This report describes performance analysis of multiphase machines. There has been a growing interest in multiphase machines due to their fault tolerant feature which is suitable for reliability sensitive applications like aerospace, hybrid vehicles and traction. There is a need to study different aspects of these machines in further detail for commercial realization. In this report, FEM simulation results of multiphase machines are presented with focus on the 6-phase machines. A comprehensive comparison of multiphase machines in general and the 6-phase machine in particular has been presented. In the 6-phase machines, there are no contributions of the 5th, 7th, 17th and 19th harmonics from the stator. This feature eliminates 6th and 18th torque pulsations and rotor surface losses are reduced. Total losses of the 6-phase machines are usually lower. However amount of loss reduction is topology dependant. In induction machines, loss reduction can be variable depending upon star or delta connection. Loss reduction in PM machines is rotor design dependant. Low order MMF harmonics from the stator are further eliminated with increasing phase number. The value of THD drops when going from a 3-phase to a 12-phase machine. The 6-phase synchronous machine is evaluated in further depth which shows drop in damper bar losses for sinusoidal supply when analyzing affects of possible supply angle mismatch from the converter. It is shown that the 6-phase machine is sensitive to supply angle mismatch. Total losses of the machine increase with increase of deviation from 30 degrees supply angle. A comprehensive study is made on the influences of parameters, such as winding layout, wedge material properties and rotor pole shape of a 3-phase synchronous machine and results are compared with the 6-phase machine. Both machines are already well optimized for individual parameters. However, from space harmonics point of view, use of short pitch, magnetic wedge and arched pole is helpful to reduce rotor surface losses with a slight increase of total losses. The 6-phase machine is more suited to these changes. Although, total losses of the machine are slightly higher, yet there is a decrease of rotor surface losses. A detailed study of the induction and the PM machine is suggested as future work.
Keywords: Elkraftteknik; Electric power engineering